SERBO-BYZANTINE RELATIONS IN THE WERY LAST DECADE OF XI CENTURY: VOLKAN’S MILITARY INTRUSION TO THE POLOG (Annual of the Faculty of Philosophy in Skopje, 2010)
During the Serbian-Byzantium border turbulences in the first half of the very last decade of XI Century, in the interval the end of 1093 - January 1194, North-Western Macedonian region Polog-part of Byzantium, have been devastated of Serbian military forces led by zhupan Volkan(os) and suffered from Serbian plundering activities.
Keywords: POLOG; BYZANTIUM; ALEKSIY I KOMNIN; ANA KOMNINA; MEDIEVAL SERBIA; RASHKA; ZHUPAN OF RASHKA; VOLKAN